Efektivitas Media Pembelajaran Papan Perkalian Dalam Peningkatkan Kemampuan Operasi Hitung Perkalian 1–5 Pada Anak Dengan Disabilitas Intelektual Ringan - Duke Ulima Rahma; Johandri Taufan; Nurhastuti Nurhastuti; Setia Budi (Lembaga Riset dan Inovasi Almatani, 2026)
This study aimed to examine the effectiveness of multiplication board learning media in improving multiplication operation skills of numbers 1–5 in a tenth-grade student with mild intellectual disability at SLB Work Shop Padang. The study employed a Single Subject Research (SSR) method with an A–B design. The research subject was one student with mild intellectual disability. The baseline phase (A) was conducted over three sessions and showed an initial multiplication operation ability of 30%. Subsequently, the intervention phase (B) was implemented over seven sessions using multiplication board learning media, resulting in a gradual improvement in multiplication operation skills with achievement levels ranging from 70% to 100%. Data were collected through observation, while data analysis was carried out using visual graph analysis to examine changes in the subject’s performance across each research phase. The findings indicate that multiplication board learning media are effective in improving multiplication operation skills of numbers 1–5 in students with mild intellectual disability. The novelty of this study lies in the use of multiplication boards as concrete and visual learning media that support the understanding of basic multiplication concepts in accordance with the learning characteristics of students with mild intellectual disability.